Manfaat Akuntansi Basis Akrual dan Akuntansi Basis Kas Menuju Akrual dalam Pengambilan Keputusan Internal Pemerintah Daerah - Ferryono, Baries; Sutaryo, Sutaryo (Jurnal Dinamika Akuntansi dan Bisnis, 2017)
This study explores how accrual accounting and cash accounting resulted information used by Indonesian local goverment managers in making decision.it is a descriptive quantitative method research. Data was collected from questionnaires consists of 19 questions related to internal decision making in the local goverments. The respondences were managers of local goverments in East java Province and West Sulawesi Province. The results demonstrated that accrual accounting method provided more useful information than cash toward accrual accounting method. In addition, the respondences reported that they did not have adequate capacilities to use utilize accrual accounting method. Thus, they need further training.